1986
DOI: 10.1046/j.1537-2995.1986.26587020124.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of irradiation on stored platelets

Abstract: Platelet concentrates intended for transfusion to immunosuppressed patients are irradiated to minimize transfusion-induced graft-versus-host disease. Because few reports describe how irradiation influences stored platelets, the authors studied whether 5000 rad of gamma irradiation, the maximum dose currently used clinically, altered platelets in vitro. Platelet concentrates were stored for either 1 day or 5 days in plastic (PL 732) containers before gamma irradiation. One unit of a pair of identical platelet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 12 publications
3
24
0
2
Order By: Relevance
“…Under no test conditions did discontinuous agitation affect a change great enough to result in any value outside the range expected for stored PCs on the basis of previous studies. 12,13 The results from this study confirm and extend the results of Simon and Sierra, 6 who showed that PCs could be transported to distant locations early in the PC's shelf life. We found that an interruption of continuous agitation for a 1 or 2 day period did not excessively accelerate the production of lactic acid, so that it did not result in a drop of pH levels to less than 7.0 on Day 5 of storage; contradicting the data presented by Hunter et al 5 They concluded that the increase in production of lactic acid occurs while agitation is interrupted.…”
Section: Resultssupporting
confidence: 87%
“…Under no test conditions did discontinuous agitation affect a change great enough to result in any value outside the range expected for stored PCs on the basis of previous studies. 12,13 The results from this study confirm and extend the results of Simon and Sierra, 6 who showed that PCs could be transported to distant locations early in the PC's shelf life. We found that an interruption of continuous agitation for a 1 or 2 day period did not excessively accelerate the production of lactic acid, so that it did not result in a drop of pH levels to less than 7.0 on Day 5 of storage; contradicting the data presented by Hunter et al 5 They concluded that the increase in production of lactic acid occurs while agitation is interrupted.…”
Section: Resultssupporting
confidence: 87%
“…during a 5-day storage period. 16,17 Many studies have shown that a drop in the pH during storage to 6.4 or 6.2 causes swelling of the platelets and a decrease in the number of transfused platelets. A pH value <6.1 has been reported to result in irreversible shape changes in transfused platelets and a pH value <6.2 results in a 50% decrease in the number of platelets remaining in circulation after transfusion and a 50% decrease in the half-life of the platelets in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported studies of in vitro function and in vivo survival have looked at the effect of 50 Gy [5,13]. Using this dose, Moroff et al [13] measured various parameters of platelet The reason for the impaired recovery after 5-day storage is likely to be multifactorial but appears to result from an increasing proportion of platelets becoming non-viable with increased storage times. If the Cl are expressed as a ratio of 20-hour to I-hour recovery (table 3), there is no significant difference related to storage time.…”
Section: Discussionmentioning
confidence: 99%